PARADIGMA KEPEMIMPINAN PENDIDIKAN DALAM MENYONGSONG EKOTEOLOGI DI ERA DISRUPSI - Siswadi Siswadi (Jurnal Manajemen Pendidikan, 2024)
Strengthening the paradigm of eco-theological-based educational leadership is important in this era of disruption marked by technological developments and increasing environmental crises. This study aims to examine the integration of theological and ecological values in educational leadership. The study uses a qualitative approach with a library research method through the analysis of various relevant books, journal articles, and academic documents. The results of the study show that the eco-theological paradigm of educational leadership integrates a theocentric perspective that places God as the source of moral and spiritual values and an ecocentric perspective that emphasizes a harmonious relationship between humans and nature. The integration of these two perspectives encourages ethical awareness in preserving the environment through the development of an environmentally-friendly curriculum and the formation of a green school culture. This approach is expected to encourage adaptive educational leadership practices that are oriented towards environmental sustainability.